2011
DOI: 10.1097/mph.0b013e3181fd6fca
|View full text |Cite
|
Sign up to set email alerts
|

Twice Weekly Pneumocystis jiroveci Pneumonia Prophylaxis With Trimethoprim-Sulfamethoxazole in Pediatric Patients With Acute Lymphoblastic Leukemia

Abstract: Twice weekly TMP/SMX seems to be a reasonable alternative for PCP prophylaxis for pediatric ALL patients. In review of other recent publications on pediatric patients, this recommendation can likely be extended to other pediatric malignancies as well. Further study is required to determine the appropriate length of prophylaxis and whether once weekly TMP/SMX prophylaxis or SMX alone at current or smaller doses could provide effective prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…Four studies included only patients with acute lymphoblastic leukaemia11–13 18 while the remainder included children with a range of haematological malignancies and solid tumours. The number of days per week of dose administration was: 7 days that is, continuous (six studies), 3 days (two studies), 2 days (four studies), 2 or 3 days (one study) and 1 day (one study).…”
Section: Commentarymentioning
confidence: 99%
“…Four studies included only patients with acute lymphoblastic leukaemia11–13 18 while the remainder included children with a range of haematological malignancies and solid tumours. The number of days per week of dose administration was: 7 days that is, continuous (six studies), 3 days (two studies), 2 days (four studies), 2 or 3 days (one study) and 1 day (one study).…”
Section: Commentarymentioning
confidence: 99%
“…Institutional practice may recommend CT of the chest, abdomen and pelvis in neutropenic patients with ≥5 days of persistent fever although a recent pediatric study challenges this practice (Agrawal et al 2011 ). Specifi cally, for 52 children with 68 episodes of FN for whom CT (sinuses, chest, abdomen and pelvis) was performed at day fi ve of fever, minimal changes in clinical management occurred based upon results from imaging.…”
Section: Computed Tomography (Ct)mentioning
confidence: 99%
“…In an analysis of 221 ALL patients with hyperleu kocytosis (WBC ≥200 × 10 9 /L) treated on the Scandinavian NOPHO trials, only initial uric acid levels (11.0 versus 7.7 mg/dL) was signi fi cant in multivariate analysis for TLS risk (WBC count and LDH were not signifi cant) (Vaitkevičienė et al 2013 ). Consensus guidelines consider LDH >2× ULN and WBC >25 × 10 9 /L as risk factors for the development of LTLS although it is unclear whether these factors are true measures for risk of CTLS, especially in pediatric patients (Table 3.2 ) (Coiffi er Tosi et al 2008 ;Cairo et al 2010 ;Agrawal and Feusner 2011 ;Pession et al 2011 ). Montesinos et al ( 2008 ) found that LDH > upper limit of normal (ULN), creatinine >1.4 mg/dL, hyperuricemia (uric acid >7.5 mg/ dL), and WBC >25 × 10 9 /L were all signifi cant risk factors for both LTLS and CTLS in adult AML patients and subsequently validated a risk scoring system.…”
Section: Laboratory Risk Factors For Tumor Lysismentioning
confidence: 99%
“…En niños con LLA, no se reportó caso alguno de infección por P. jiroveci, con un esquema profiláctico de cotrimoxazol indicado dos días consecutivos por semana 11,12 .…”
Section: Trasplante De Precursores Hematopoyéticosunclassified